STUDY KEBUTUHAN AIR BERSIH DI WILAYAH PELAYANAN PDAM CABANG LOA KULU KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - PRASETYO, HERI NOTO (KURVA S JURNAL MAHASISWA, 2017)
Water in human life has a very vital function. Water is needed in everyday activities, such as for bathing, washing, and cooking. Even most the human body also consists of water.Currently, the service in Water Utilities Branch Loa Kulu has a coverage of 53.1%. This coverage is far from the stipulated requirement of 90%. Therefore, it is necessary to review the need of clean water for the service area of Loa Kulu Water Utilities Branch in the present and future, so that the need of the residents of Loa Kulu for clean water can be fulfilled.The method of the research is by collecting current population data and the resulting water capacity data. That way we can project the number of population and how much water needed in the planned years of 2021, 2026, 2031 and 2036.From the result, it can be concluded that the need for clean water in Water Utilities service area of Loa Branch for 2021, 2026, 2031, 2036 are Q = 131,360 liters/second, 156,084 liters/second, 180,809 liters/second, and 205,532 liters/second.